PENGEMBANGAN KURIKULUM PAUD BERBASIS KEARIFAN LOKAL DALAM PERSPEKTIF P5 DI TK DIDAKTIKA USWATUN KHASANAH BEJI PURWOKERTO - Rohyati, Rohyati; Wiyani, Novan Ardy (Universitas PGRI Semarang, 2023)
This study aims to look at and analize the development of a local wisdom-based PAUD curriculum in the P5 perspective applied in the Kindergarten Didaktika Uswatun Khasanah Beji. Because not all educational institutions, especially Early Childhood Education, have been able to implement the PAUD Curriculum system based on local wisdom in accordance with the existing programs in P5. That way the author is very interested in being able to dig deeper into the application of the PAUD Curriculum that is implemented in the Kindergarten Didaktika Uswatun Khasanah Beji. The PAUD Curriculum that is implemented civers several aspects for the sake of improving the quality and quality of schools, especially the quality of child development. The results show that the implementation of the PAUD Curriculum based on local wisdom in the Kindergarten Didaktika Uswatun Khasanah Beji has many positive impacts for both school institutions, teachers and students, and the environment around the Kindergarten. Teachers or intructors become more professional in determining the concepts and structures of learning implemented in schools. In addition, students are also more skilled, independent, and synergized in instilling a social and religious spirit with noble character. The success of the quality and quality of schools can be seen from the developments that occur in children. The method in this study uses qualitative research methods. The type of research used is the phenomenological approach. Where the reseracher examines a phenomenon that is experienced in the real world, namely the application of P5 in the Didaktika Uswatun Khasanah Beji Purwokerto Kindergarten. Research is conducted to be understood and studied the truth. Submission of research into the discussion descriptively.